2022
DOI: 10.1002/pits.22764
|View full text |Cite
|
Sign up to set email alerts
|

Secondary trauma, burnout, and teacher self‐care during COVID19: A mixed‐methods case study

Abstract: Manifestations of teacher burnout have been negatively associated with students' academic achievement, school satisfaction, and perceived teacher support. The 2020–2021 school year presented unique challenges for teachers, who had to find new ways to support their students, their families, and themselves. This study examined teachers' experiences with secondary trauma, burnout, and self‐care during COVID‐19 at one K‐5 trauma‐informed school, the Wellington (pseudonym). We chose a mixed‐methods convergent desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…According to Güler and Yöndem (2021), when psychological resilience levels drop, individuals' capacity to cope with challenges wanes, and burnout levels increase. McMakin et al (2022) spotted a low level of secondary traumatic stress and a moderate level of burnout among teachers during this period. Although our study does not delve into the trauma aspect, the low scores indicate that further scrutiny is warranted concerning the impact of the pandemic on teachers' life purposes and relationships.…”
Section: Discussion and Resultsmentioning
confidence: 86%
“…According to Güler and Yöndem (2021), when psychological resilience levels drop, individuals' capacity to cope with challenges wanes, and burnout levels increase. McMakin et al (2022) spotted a low level of secondary traumatic stress and a moderate level of burnout among teachers during this period. Although our study does not delve into the trauma aspect, the low scores indicate that further scrutiny is warranted concerning the impact of the pandemic on teachers' life purposes and relationships.…”
Section: Discussion and Resultsmentioning
confidence: 86%
“…Even as the COVID-19 pandemic continued, data collected early in the 2020-2021 school year found that teachers had high levels of burnout and anxiety (Hirshberg et al, 2023;McMakin et al, 2023;Pressley, 2021;Trinidad, 2021). For instance, Hirshberg and his colleagues (2023) explored mental health of teachers and school staff members.…”
Section: Teacher Burnout and Mental Healthmentioning
confidence: 99%
“…Ingersoll and Tran (2023) found that the result has been a rise in teacher attrition, which in turn has placed additional responsibility and stress on the educators who remain. This complex, intensive workload, alongside lacking support, has increased teachers' stress to an unprecedented level, making our profession vulnerable and susceptible to the current teacher turnover and widespread shortages experienced throughout the nation Goldberg, 2021;Ingersoll & Tran, 2023;McMakin et al, 2022;Zamarro et al, 2021). Hendershott and Hendershott (2020) argued that educators must intentionally implement self-care strategies as the first step to managing the negative impact brought on by experiencing secondary trauma, along with added stressors in the classroom.…”
Section: Literature Reviewmentioning
confidence: 99%